9H-purine scaffold reveals induced-fit pocket plasticity of the BRD9 bromodomain - Picaud, S; Strocchia, M; Terracciano, S; Lauro, G; Mendez, J; Daniels, D; Riccio, R; Bifulco, G; Bruno, I; Filippakopoulos, P (American Chemical Society, 2015)
The 2-amine-9H-purine scaffold was identified as a weak bromodomain template and was developed via iterative structure based design into a potent nanomolar ligand for the bromodomain of human BRD9 with small residual micromolar affinity toward the bromodomain of BRD4. Binding of the lead compound 11 to the bromodomain of BRD9 results in an unprecedented rearrangement of residues forming the acetyllysine recognition site, affecting plasticity of the protein in an induced-fit pocket. The compound does not exhibit any cytotoxic effect in HEK293 cells and displaces the BRD9 bromodomain from chromatin in bioluminescence proximity assays without affecting the BRD4/histone complex. The 2-amine-9H-purine scaffold represents a novel template that can be further modified to yield highly potent and selective tool compounds to interrogate the biological role of BRD9 in diverse cellular systems.